Zoonotic Cryptosporidium spp. in Wild Rodents and Shrews - Rauni Kivistö; Sofia Kämäräinen; Otso Huitu; Jukka Niemimaa; Heikki Henttonen (Microorganisms, 2021)
There has been a significant increase in the number of reported human cryptosporidiosis cases in recent years. The aim of this study is to estimate the prevalence of Cryptosporidium spp. in wild rodents and shrews, and investigate the species and genotype distribution to assess zoonotic risk. Partial 18S rRNA gene nested-PCR reveals that 36.8, 53.9 and 41.9% of mice, voles and shrews are infected with Cryptosporidium species. The highest prevalence occurred in the Microtus agrestis (field vole) and Myodes glareolus (bank vole). Interestingly, bank voles caught in fields were significantly more often Cryptosporidium-positive compared to those caught in forests. The proportion of infected animals increases from over-wintered (spring and summer) to juveniles (autumn) suggesting acquired immunity in older animals. Based on Sanger sequencing and phylogenetic analyses, Apodemus flavicollis (yellow-necked mouse) is commonly infected with zoonotic C. ditrichi. Voles carry multiple different Cryptosporidium sp. and genotypes, some of which are novel. C. andersoni, another zoonotic species, is identified in the Craseomys rufocanus (grey-sided vole). Shrews carry novel shrew genotypes. In conclusion, this study indicates that Cryptosporidium protozoan are present in mouse, vole and shrew populations around Finland and the highest zoonotic risk is associated with C. ditrichi in Apodemus flavicollis and C. andersoni in Craseomys rufocanus. C. parvum, the most common zoonotic species in human infections, was not detected.